Implementasi Sistem IoT Pada Akuakultur Dan Hydroponik (Akuaponik) Modern Untuk Pertumbuhan Ikan Nila - Setiawan, Bagas; Styawati, Styawati; Alim, Syahirul (Politeknik Harapan Bersama, 2024)
In modern times, there are many types of agricultural and fish farming systems, one of which is the modern aquaculture system which has been recognized as an innovative method of sustainable food production that combines fish cultivation with agriculture simultaneously. Modern aquaponics is able to overcome problems in urban areas which require land for growing crops and cultivating fish. Good fish cultivation means always monitoring the growth and health of fish to reduce the risk of crop failure, therefore this research aims to implement an Internet of Things (IoT) system in modern aquaponics to increase the growth of tilapia. IoT parameters consisting of pH sensors, Total Dissolved Solids (TDS) sensors, and temperature sensors are used to monitor water quality conditions in modern aquaponics. Through IoT systems, data collected in real-time enables more effective environmental monitoring. The creation of an IoT system in modern aquaponics shows that the implementation of IoT can increase the efficiency of modern aquaponic environmental management, resulting in better fish growth and plant productivity. This was verified through the pH sensor test results with a value of 7.2 indicating optimal conditions of acid-base balance in the water, which is essential for the health of tilapia fish. The TDS sensor test with a value of 300 ppm confirmed that the concentration of solid particles in the water was at an optimal level, which is also an indicator of the health of the tilapia fish. Temperature measurement using a temperature sensor with a value of 28°C, shows that the water temperature is within the ideal range for comfort for tilapia, which is usually comfortable at temperatures between 28-30°C